Designed supramolecular filamentous peptides: balance of nanostructure, cytotoxicity and antimicrobial activity. Issue 7 (5th December 2014) - Xu, Dawei; Jiang, Linhai; Singh, Anju; Dustin, Derek; Yang, Miao; Liu, Ling; Lund, Reidar; Sellati, Timothy J.; Dong, He
Abstract : We present a design strategy to optimize antimicrobial peptides to minimize cytotoxicity while enhancing stability and antimicrobial activity, which holds promise for local and systemic intracellular anti-infective therapy. Abstract : This work demonstrates a design strategy to optimize antimicrobial peptides with an ideal balance of minimal cytotoxicity, enhanced stability, potent cell penetration and effective antimicrobial activity, which hold great promise for the treatment of intracellular microbial infections and potentially systemic anti-infective therapy.